2009 IEEE 17th International Conference on Program Comprehension 2009
DOI: 10.1109/icpc.2009.5090048
|View full text |Cite
|
Sign up to set email alerts
|

Vector space analysis of software clones

Abstract: In this paper, we introduce a technique for applying Independent Component Analysis to vector space representations of software code fragments such as methods or blocks. The distance between these points can be determined, and used as a measure of the similarity between the original source code fragments they represent. It can be reasoned that if the initial matrix representation contains enough information about the syntactic structure of the source code, the vector space representation will be sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…a clear relationship between proximity in the package structure and the likelihood of finding clones [33]. Using this, together with our observation that clones often share similar semantic information and are frequently identified as semantically related in latent models [30], we believe that the proximity score is a reasonable measure.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…a clear relationship between proximity in the package structure and the likelihood of finding clones [33]. Using this, together with our observation that clones often share similar semantic information and are frequently identified as semantically related in latent models [30], we believe that the proximity score is a reasonable measure.…”
Section: Resultsmentioning
confidence: 91%
“…In our earlier research using information retrieval methods to locate clones [30], the results suggested a correlation between clones and latent topics. While it is not true that all clones are conceptually related, they are more likely to be conceptually related than not.…”
Section: Code Localitymentioning
confidence: 99%
See 1 more Smart Citation
“…Grant and Cordy [17] introduced a technique based on independent component analysis to analyze vector space representations of methods in software systems.…”
Section: Related Workmentioning
confidence: 99%
“…Local weights range in complexity from simple binary values (0 or 1) to functions involving logarithms of term frequencies. Global weighting schemes range from simple normalizations to advanced statistics-based approaches [3,17].…”
Section: Vector Space Modelmentioning
confidence: 99%